2019
DOI: 10.1590/s2175-97902019000217649
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of photoprotective formulations containing keratin particles

Abstract: This work deals with development and evaluation of MFQ protective formulation, which contains two organic filters, namely: octyl-p-methoxycinnamate (OMC) and benzophenone-3 (BP-3); a photostabilizing agent called ethylhexylmethoxycrylene (EHMCR) and keratin particles. The MFQ formulation was evaluated in order to measure its pH, spin-spin lattice relaxation time (T 2 H), occlusivity factor, formulation efficacy, photostability and skin permeation, as well as keratin particle properties. Keratin particle size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The SPF, UVA/UVB ratio, and λc values of the emulsions were evaluated after exposure to SSL irradiation using a solar simulator (Oriel Model 91192-1000, Newport Corp., USA) according to the following procedure: a 50 mg (2 mg/cm 2 ) amount of each formulation was homogeneously distributed on quartz plates with a 25 cm 2 area; the plates were then exposed to an SSL simulator and SPF, UVA/UVB ratio and λc were determined at nine points on the plates by Integration Sphere Transmittance Spectrophotometry (Labsphere UV-2000S). Irradiation conditions were as previously described, but with a 2 h exposure, following the recommendation to reapply sunscreen products every two hours (Coutinho et al, 2015;FDA, 2012;Teixeira et al, 2019).…”
Section: Photostability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The SPF, UVA/UVB ratio, and λc values of the emulsions were evaluated after exposure to SSL irradiation using a solar simulator (Oriel Model 91192-1000, Newport Corp., USA) according to the following procedure: a 50 mg (2 mg/cm 2 ) amount of each formulation was homogeneously distributed on quartz plates with a 25 cm 2 area; the plates were then exposed to an SSL simulator and SPF, UVA/UVB ratio and λc were determined at nine points on the plates by Integration Sphere Transmittance Spectrophotometry (Labsphere UV-2000S). Irradiation conditions were as previously described, but with a 2 h exposure, following the recommendation to reapply sunscreen products every two hours (Coutinho et al, 2015;FDA, 2012;Teixeira et al, 2019).…”
Section: Photostability Assaymentioning
confidence: 99%
“…The photostability of sunscreen formulations measures the stability of UV filters against solar radiation and is an important factor that should be considered during the development of sunscreen formulations. The present formulations were irradiated for 2 hours, which is the period recommended for the reapplication of a sunscreen (Teixeira et al, 2019).…”
Section: Photostability Assaymentioning
confidence: 99%
“…The amount of residual water in each glass container was analyzed after 6, 24 and 48 hours by the weight of the systems. A system without formulation was used as reference (Teixeira et al, 2019).…”
Section: Occlusivity Testmentioning
confidence: 99%
“…(Equation 5) where A stands for the water loss in the container without sample (reference) and B is the water loss in the container with sample. The occlusion factor can vary from 0 to 100: zero means non-occlusive effect and 100 is maximum occlusion (Wissing, Müller, 2002;Teeranachaideekul et al, 2008;Teixeira et al, 2019)…”
Section: Occlusivity Testmentioning
confidence: 99%
“…In the HLB study, it was found that the adequate content of surfactant Tween™ 80 was 10%. Further, the percentage of different components of emulsions was chosen according to Teixeira et al (2019). The O/W emulsions were prepared using the standard methods with a mechanical processor (Fisaton-718).…”
Section: Development Of Emulsionmentioning
confidence: 99%